Effect of COVID-19 Home Confinement on Family Well-Being - Rooban Thavarajah; Anusa Arunachalam Mohandoss; Kannan Ranganathan (Wolters Kluwer Medknow Publications, 2020)
Introduction: Home confinement (HC) due to Corona Virus Disease-19 (COVID-19) creates changes in family dynamics. A survey tool was developed based on existing tools to measure the changes in family attachment, bonding, changeability, and interaction during HC. The aim was to capture the changes in family well-being in a defined cohort of dentists and observe the role of sociodemographic factors in such a change. Material and Methods: A new tool "home containment mediated family improvement index (HCMFII)" was developed, pretested, and used for measuring the changes in family well-being. The survey intended to capture the basic demographic details along with HCMFII. This was developed as a Google form and circulated among Indian dentists for 72 hours from 29 May to 1 June. Descriptive statistics, measures of association, and one-way analysis of variance (ANOVA) were used to identify the difference between the demographic factors and HCMFII scores. P ≤ 0.05 was taken as significant. Result: In the 72 hours, 213 Indian dentists completed the survey. Of them, 37 (17.4%) had negative HCMFII scores, 56 (26.3) in neutral, and 120 (56.3%) with a positive outlook during HC compared to pre-COVID-19 situation. The mean HCMFII score was 53.9 ± 14. Age (P = 0.02), marital status (P < 0.00), children (P < 0.001), and income (P = 0.01) were significant factors influencing the scores. Discussion and Conclusion: A new tool to capture familial well-being in chrono-environment in presented. One of the two dentists perceived better family well-being, whereas one of the four perceived no change. Cause of concern is that one of the eight dentists still continue to have more disagreement-discordance than before HC and lesser family well-being. Extension of this index study would help to gauge the family well-being during HC and institute better modes of familial engagement to change the course of the pandemic.